2003
DOI: 10.1046/j.1365-2427.2003.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential fatty acids and N and P‐limited algae on the growth rate of tropical cladocerans

Abstract: SUMMARY 1. In this study, the effects of nutrient (N and P) deficiency and the importance of essential polyunsaturated fatty acids (PUFA) [eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] to tropical cladocerans, growth and reproduction were determined in a growth bioassay. 2. The animals were fed N/P‐sufficient, N‐deficient and P‐deficient algae, and also N and P‐deficient algae supplemented with fish oil emulsions rich in EPA and DHA. 3. Cladocerans showed different responses to nutrient‐deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
1
22
1
5
Order By: Relevance
“…Reductions in biomass of these groups were observed at night. Cryptophytes are extremely edible for zooplankton and contain high concentrations of PUFA (Polyunsaturated fatty acids; Ahlgren et al, 1992), and are an important food item of these herbivores (Gullati and DeMott, 1997;Ferrão-Filho et al, 2003a). An experimental study has suggested that high cryptophycean biomass in the summer may have contributed to increased growth of cladocerans in Lake Monte Alegre (Ferrão-Filho et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in biomass of these groups were observed at night. Cryptophytes are extremely edible for zooplankton and contain high concentrations of PUFA (Polyunsaturated fatty acids; Ahlgren et al, 1992), and are an important food item of these herbivores (Gullati and DeMott, 1997;Ferrão-Filho et al, 2003a). An experimental study has suggested that high cryptophycean biomass in the summer may have contributed to increased growth of cladocerans in Lake Monte Alegre (Ferrão-Filho et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Esses aspectos foram confirmados em testes sobre qualidades mineral, bioquímica e morfológica do séston do Lago Monte Alegre (Fileto et al, 2007a, b) e sobre os efeitos da limitação de nutrientes sobre o crescimento dos cladóceros (Ferrão-Filho et al, 2003b). A produção secundária de microcrustáceos influenciada por ambos os fatores, alimento e temperatura, é variável entre as espécies e entre diferentes classes etárias, como já testado por Minto (2009).…”
Section:  Variação Temporal No Lago Monte Alegreunclassified
“…A reprodução de D. gessneri é também a mais afetada pelas condições do séston no inverno em relação a outras espécies (Ferrão-Filho et al, 2003b;Fileto et al, 2007b), além de ser sensível à limitação mineral (Ferrão-Filho et al, 2003 a, b) e à presença de cianobactérias (Fileto et al, 2004). Provando a influência de cianobactérias sobre alguns daphnideos, a espécie Daphnia carinata, existente em um lago chinês, foi competitivamente inferior do que outros cladóceros pequenos na presença de altas concentrações das cianobactérias (Chen et al, 2007).…”
Section: Discussão| 58unclassified
“…Brett et al (2000) also concluded that phytoplankton food quality decreases as the C:P ratio of the algae increases above 300. Of course, at C:P > 1000, PUFAs can still be important and might not be limiting to herbivores (Ferrāo-Filho et al, 2003). At high light condition, though the rate of C fixation increases (resulting high C:P), it cannot be efficiently transferred to higher trophic level due to P-deficient food selectivity by herbivores.…”
Section: P Dependent Stoichiometric Regulation Of Food Chainmentioning
confidence: 99%